INCONSISTENCY OF LAWS ON ERADICATION OF CORRUPTION IN INDONESIA - Gustian, Leo; ansah, Ardi; Kadaryanto, Bagio (EKSEKUSI, 2024)
ABSTRACT The inconsistency of the law on eradicating criminal acts of corruption in Indonesia, especially regarding criminal acts of corruption in office or related to office, apart from not conflicting with the legal hierarchy in Indonesia, also causes the absence of legal certainty in law enforcement against criminal acts of corruption, especially corruption in office or related matters. Related to position and ostensibly to provide wide latitude for state administrators/state officials who are caught in criminal acts of bribery to escape punishment. The ideal legal concept for eradicating criminal acts of corruption in Indonesia, especially regarding criminal acts of corruption in office or related to office, is the ideal concept in Article 3 and Article 4 of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning Commissions. Eradication of Corruption Crimes. The phrase "can" which still exists in Article 3 of the regulation as well as Article 4 in the regulation makes it easier to prove cases in inquiries and investigations in police and prosecutor institutions, besides compensation for state losses does not eliminate the sanctions of imprisonment and fines, thus creating a deterrent effect. In society, there is legal certainty and equal justice for all Indonesian people.Keywords: Inconsistency, Position, Corruption ABSTRAK Inkonsistensi hukum pemberantasan tindak pidana korupsi di Indonesia terutama terhadap tindak pidana korupsi dalam jabatan atau yang berhubungan dengan jabatan, selain tidak bertentangan dengan hierarki perundang-undangan di Indonesia juga menyebabkan tidak adanya kepastian hukum dalam penegakan hukum terhadap tindak pidana korupsi terutama korupsi dalam jabatan atau yang berhubungan dengan jabatan serta seolah-olah memberikan ruang gerak yang luas bagi penyelenggara negara/pejabat negara yang terjerat dalam tindak pidana korupsi yang dimaksud untuk lepas dari pemidanaan. Konsep ideal hukum pemberantasan tindak pidana korupsi di Indonesia terutama terhadap tindak pidana korupsi dalam jabatan atau yang berhubungan dengan jabatan adalah konsep ideal dalam Pasal 3 dan Pasal 4 Undang-Undang Nomor 19 Tahun 2019 tentang Perubahan Kedua Atas Undang-Undang Nomor 30 Tahun 2002 tentang Komisi Pemberantasan Tindak Pidana Korupsi. Frasa “dapat” yang masih eksis dalam Pasal 3 regulasi tersebut serta Pasal 4 dalam regulasi tersebut memudahkan pembuktian perkara dalam penyelidikan dan penyidikan dalam institusi kepolisian dan kejaksan, selain itu penggantian kerugian negara tidak menghapuskan sanksi hukuman pidana penjara dan pidana denda, sehingga menimbulkan efek jera dalam masyrajat, adanya kepastian hukum serta keadilan yang merata bagi seluruh rakyat Indonesia.Kata Kunci: Inkonsistensi, Jabatan, Korupsi